1995
DOI: 10.1071/bt9950555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insect Herbivory on the Decline of Black Box (Eucalyptus largiflorens)

Abstract: The contribution of insect herbivory to the canopy decline of Eucalyptus largiflorens F.Muell. (black box) was assessed on nine irrigated properties around Deniliquin in southern central New South Wales. Fully expanded leaves less than 1 year old were sampled from 36 mature trees in June 1993 and again in June 1994 after half the trees had been treated with a systemic insecticide in November 1993. Insect herbivory in treated trees fell significantly from 27 to 9%. It also fell, but to a lesser extent (28-19%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…Few trees escape herbivory at some point in their lives, with the majority capable of sustaining much higher levels of leaf damage than observed in our study without obvious detrimental affects to forest health (Landsberg & Wylie 1983). Unlike elsewhere (Stone & Bacon 1995) the loss of photosynthesizing tissue through necrosis, mining and galling was the most common type of leaf damage observed in our study, with total damage levels lower than demonstrated for eucalypts in different systems elsewhere in Australia (Fox & Morrow 1983; Stone 2001). However, damage levels to eucalypt leaves vary greatly both spatially and temporally, and both within and between species (Stone et al 1998).…”
Section: Discussioncontrasting
confidence: 70%
“…Few trees escape herbivory at some point in their lives, with the majority capable of sustaining much higher levels of leaf damage than observed in our study without obvious detrimental affects to forest health (Landsberg & Wylie 1983). Unlike elsewhere (Stone & Bacon 1995) the loss of photosynthesizing tissue through necrosis, mining and galling was the most common type of leaf damage observed in our study, with total damage levels lower than demonstrated for eucalypts in different systems elsewhere in Australia (Fox & Morrow 1983; Stone 2001). However, damage levels to eucalypt leaves vary greatly both spatially and temporally, and both within and between species (Stone et al 1998).…”
Section: Discussioncontrasting
confidence: 70%
“…Each leaf sample was measured for leaf condition in three ways: (i) leaf area lost to insect herbivory (% damage) using the method described in Stone and Bacon (1995) (mean = 10.1%, σ = 6.6%, n = 22); (ii) visual estimation of percent area of red or purple discoloration on each leaf (% red) (mean = 20.08%, σ = 22.3%, n = 22); and (iii) visual estimation of percent necrosis on each leaf (mean = 8.5%, σ = 10.2%, n = 22).…”
Section: Methodsmentioning
confidence: 99%
“…The shade plots were similarly affected by herbivory as bare plots, and although the identity of the herbivores was unclear, they were most likely insects or small vertebrates. Insect herbivory is common in eucalypts and has been responsible for the dieback of mature trees throughout Australia (Landsberg and Wylie 1983;Stone and Bacon 1995). The timing of herbivory in the first month of the winter transplant experiment suggests that either the young seedlings were more susceptible to herbivory or that herbivores were more common at this time of the year.…”
Section: Discussionmentioning
confidence: 99%